Pengaruh Disiplin Kerja, Lingkungan Kerja, Dan Motivasi Kerja Terhadap Prestasi Kerja Perawat Di RSUD Kota Mataram - Miratunnisah Miratunnisah; Sulaimiah Sulaimiah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Employee career development plays an important role for employees, a clear career path is needed by employees. This study aims to determine the effect of work experience, training, work performance on the career development of BKD employees in NTB Province. The research population consisted of all BKD employees in the NTB Province, consisting of 91 respondents. In this study using multiple regression analysis techniques. This type of research is associative research. Data processing in this study uses SPSS 26 For Windows. Based on the research that has been done, it is found that work experience, training and work performance have a positive and significant influence on the career development of BKD employees in NTB ProvinThis study entitled The Effect of Work Discipline, Work Environment, and Work Motivation on Nurse Work Performance at Mataram City Hospital which aims to determine the effect of each work discipline variable (X1), work environment (X2), and work motivation (X3) on work performance (Y). The type of research used in this research is causal associative. The data collection method uses the sample method with a total population of 397 people and the number of samples taken is 80 respondents. The type of data used in this research is quantitative data. Tests in this study used an instrument test which consisted of a validity test and a reliability test then used the classic assumption test which consisted of a normality test, multicollinearity test and heteroscedasticity test. Subsequent tests use a multiple linear regression analysis model consisting of the F test, t test, and R2 test. The data analysis technique used the SPSS version 26 program. The results showed that: (1) Work discipline has a positive and significant effect on work performance (2) Work environment has a positive and significant effect (3) Work motivation has a positive but not significant effect on work performance.